Trisubstituted thiazoles as potent and selective inhibitors of Plasmodium falciparum protein kinase G (PfPKG). Issue 19 (15th October 2018) - Tsagris, Denise J.; Birchall, Kristian; Bouloc, Nathalie; Large, Jonathan M.; Merritt, Andy; Smiljanic-Hurley, Ela; Wheldon, Mary; Ansell, Keith H.; Kettleborough, Catherine; Whalley, David; Stewart, Lindsay B.; Bowyer, Paul W.; et al.
Graphical abstract: Highlights: A series of thiazole compounds inhibit the malarial kinase Pf PKG. SAR development of this series led to compound23. 23 has a biochemical potency of 2 nM and an in vitro cellular potency of 113 nM. 23 also possesses good in vitro ADME and excellent kinase selectivity. Abstract: A series of trisubstituted thiazoles have been identified as potent inhibitors of Plasmodium falciparum (Pf) cGMP-dependent protein kinase ( Pf PKG) through template hopping from known Eimeria PKG ( Et PKG) inhibitors. The thiazole series has yielded compounds with improved potency, kinase selectivity and good in vitro ADME properties. These compounds could be useful tools in the development of new anti-malarial drugs in the fight against drug resistant malaria.